Desain Lembar Kerja Mahasiswa dan Tes Kreativitas Ilmiah Untuk Meningkatkan Kreativitas Mahasiswa Universitas Terbuka - Asrining Surasmi, Wuwuh; Suparti; Dwikoranto (Universitas Negeri Surabaya, 2025)
This research aims to produce valid and effective Student Activity Sheets (LKM) and Creativity Tests (TKI) to increase the creativity of PGSD students. LKM and TKI are said to be valid if the content validity and construct validity scores reach a minimum score of 2.50 in the valid category and are said to be effective if there is an increase in students' scientific creativity which is statistically significant at α = 5%, the average N-gain is at least in the medium category. The design of this research is Educational Design Research. The research trial design used Pre-Experiment with a one group pre-test and post-test design. The research subjects were undergraduate students of PGSD UPBJJ Surabaya for the 2024/2025 academic year. The instruments used to collect data in this research include the LKM and TKI Validity Assessment Sheet, as well as the TKI test sheet. The research data in the form of pre-test scores and post-test scores that have been collected are tested for prerequisites: normality test and homogeneity test which are then analyzed using a paired t-test to determine whether there are differences in pre-test scores and post-test scores for students' scientific creativity. The average level of increase in pre-test scores and post-test scores is calculated using N-gain. The validity of learning tools is analyzed to determine their validity and reliability. The same analysis was carried out on the Research Instrument scores. The results of the research show that LKM and TKI are valid and reliable so they are ready to use and are effective for measuring student creativity. Keywords: LKM, TKI, Creativity